Biomechanical Bases of Forecasting Occurrence of Carotid Atherosclerosis - Kuzyk Yu.I; Ivanov D.V; Dol A.V (Annals of Circulation - Peertechz Publications, 2016)
Breast lymphomas are a rare sighting and image findings are non-pathognomonic often mimicing different forms of invasive breast cancer. Nevertheless, multimodal imaging and subsequent histopathology are crucial for diagnosis and treatment. To draw attention to this very rare entity, we present a case of a 74 year old female patient with a tumorous mass in the left maxillary sinus. The subsequent wholebody staging CT revealed an additional multicentric lesion of the right breast suggesting breast cancer. Histopathology of both lesions resulted in the diagnosis of a diffuse large B cell lymphoma (DLBCL).